The Role of Community in Crowdfunding Success: Evidence on Cultural Attributes in Funding Campaigns to "Save the Local Theater". (16th November 2016) - Josefy, Matthew; Dean, Thomas J.; Albert, Lumina S.; Fitza, Markus A.
Abstract : Despite increased interest in examining the factors that influence crowdfunding success, the effects of community context have been relatively unexamined. We address this void by examining the role of cultural context in crowdfunding success. Our unique data set of crowdfunding projects to "save the local theater" are homogenous in their goal, allowing us to test whether crowdfunding campaigns in certain communities lead to better funding outcomes than others. Theoretically, our results suggest the need for further integration of community and cultural constructs into models of venture funding, as such variables may have more relevance than previously believed.